Avaliação da atividade fotocatalítica de partículas de WO3:TiO2 obtidas pela técnica de moagem de alta energia - Faleiros, Raphael Rodrigues (2016)
The dyes effluent are toxic to microorganisms, aquatic ecosystem and humans. In this scenario has been desired effective ways to treat textile industrial wastewater in an attempt to reduce the imminent risk of contamination. A method of treatment applied to this residue are the Advanced Oxidation Processes (AOP) by heterogeneous photocatalysis, which stands out in this scenario acting on the mineralization of organic fluent, such as dyes. This study aimed to obtain, characterization and evaluation of a system oxides (WO3: TiO2), acting as a photocatalyst in the degradation of Rhodamine-B dye. The powders of different compositions of these oxides (100, 70, 50, 30 and 0% WO3) were processed through the High Energy Milling (HEM). The precursor oxides were characterized by the techniques of Nitrogen physisorption, pycnometer Helium, Differential Scanning Calorimetry and Thermogravimetry, Ray Diffraction X and scanning electron microscope (SEM-FEG). The milling for different compositions studied, happened at dry for times of 2, 4 and 8 hours. The powders obtained by HEM were characterized by X-ray diffraction, SEM-FEG. They were subjected to photocatalytic evaluation trials and oxygen consumed tests. The results indicate that the precursor oxides and processed into HEM present crystalline phases Anatase and Monoclinic, respectively, for TiO2 and WO3. The crystallite size calculations performed for the samples after grinding, indicated obtaining powders in the nanometer scale, ranging from 161 to 100 nm. The distributions and average particle sizes were calculated from the microscopy images, verifying that the grinding led to the refinement of powder, being observed in the sample with 50% WO3 and 50% TiO2 processed by HEM for 8 hours (50W8), average size of 123,68 ± 29,35 nm and 1,05 ± 0,42 µm respectively for the particles of TiO2 and WO3. Regarding photocatalytic tests, compositions processed by HEM showed an improvement in the photocatalytic activity to the extent that it increased the titania content and grinding time. Oxygen consumption measurements corroborate the results of the partial degradation of dye during the photocatalysis tests, reaching values of up to 87% degradation. It was also noted that the grinding time, the powder disintegration, chemical composition and hardness of the raw materials are extremely important factors in the case of photobleaching and that these factors can not be evaluated in isolation.